2018
DOI: 10.1002/jcp.27161
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of A2 adenosine receptor pharmacological regulators in the treatment of cardiovascular diseases, recent progress, and prospective

Abstract: Adenosine and its analogs are of particular interest as potential therapeutic agents for treatment of cardiovascular diseases (CVDs). A2 adenosine receptor subtypes (A2a and A2b) are extensively expressed in cardiovascular system, and modulation of these receptors using A2 adenosine receptor agonists or antagonists regulates heart rate, blood pressure, heart rate variability, and cardiovascular toxicity during both normoxia and hypoxia conditions. Regulation of A2 adenosine receptor signaling via specific and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The adenosinergic system also plays a key role in cardiovascular pathophysiology, as adenosine receptors are expressed on most cell types in the cardiovascular system such as cardiomyocytes, endothelial cells, vascular smooth muscle cells, pericytes, and fibroblasts [1]. Adenosine receptors have been therefore evaluated as targets for the development of new therapeutic or diagnosis options for the cardiovascular system [2,3,4,5]. The goal of this review is to present experimental evidence supporting the existence and implication in cardiovascular disorders of specific adenosinergic pharmacological profiles agreeing with the concept of “receptor reserve” also known as “spare receptors” [6].…”
Section: Adenosine and Its Receptorsmentioning
confidence: 99%
“…The adenosinergic system also plays a key role in cardiovascular pathophysiology, as adenosine receptors are expressed on most cell types in the cardiovascular system such as cardiomyocytes, endothelial cells, vascular smooth muscle cells, pericytes, and fibroblasts [1]. Adenosine receptors have been therefore evaluated as targets for the development of new therapeutic or diagnosis options for the cardiovascular system [2,3,4,5]. The goal of this review is to present experimental evidence supporting the existence and implication in cardiovascular disorders of specific adenosinergic pharmacological profiles agreeing with the concept of “receptor reserve” also known as “spare receptors” [6].…”
Section: Adenosine and Its Receptorsmentioning
confidence: 99%
“…The effectiveness of this method in modulating BBB has already been proven for the agonists of the bradykinin B2 receptor—RMP-7 [ 111 ]. In turn, the intrathecal injection of an adenosine agonist (A2 agonist-CPCA) influenced the cardiovascular system, causing a decrease of blood pressure and heart rate in rats [ 112 ]. A promising direction seems to be the synthesis of nanoparticles functionalized with ligands, e.g., antibodies.…”
Section: Adenosine Receptorsmentioning
confidence: 99%
“…It has studied that the dysfunction of these receptors stimulates CVDs, but the exact pathological mechanisms behind these A2 receptors are not available so far. 46 Stem cell transplantation has received much attention for balancing and regulating cardiac properties. Several studies indicated that stem cells could improve the heart functions through their release of paracrine signals and then networking with tissues or organs.…”
Section: Different Treatment Strategies For Cvdsmentioning
confidence: 99%